CORRELATION OF PROBLEMATIC SMARTPHONE USE AND TEXT NECK SYNDROME AMONG UNIVERSITY STUDENTS - Aljwary, Bashar J; Alyouzbaki, Farouk M (Antis-Publisher, 2024)
Background: The daily use of smartphone devices is increasing worldwide. It can affect personal relationships mental and physical health state. Neck Pain take a great deal on daily health care practice. Neck pain is considered a fourth leading cause of disability. Aim: To investigate the relationship between addiction to smartphone usage and self-reported neck pain, and to assess the predictive factors of the smartphone addiction among university students to better understand this relationship. Objective : To evaluate the association of neck pain with smartphone use and their usage duration among students of Mosul University , and correlate its use with neck pain. Method: The study examined 164 healthy students of nursing college in Mosul University by random table sampling, in the age group of 20-25 years. They were given self-administered, pre-tested questionnaire which include various mental and physical health symptoms related to smart phone usage and fill a questionnaires of Smartphone Addiction Scale (SAS), Neck Disability Index (NDI). Spearman correlation coefficient was used to correlate between the SAS and NDI. Result: Most of students (61.2%) are regular users of smartphones.47.6%had no neck pain, There is an association between SAS&NDI in male students, and there is high association of type of device use& NDI with female gender. Conclusions: The excessive use of smart phones has health related problems, more specifically in neck region. The smart phone users complain from neck pain (Text neck), more clearly related to the duration of use of smart phones.